2008
DOI: 10.1021/cm703463s
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Magnetism of EuS Nanoparticles

Abstract: EuS nanoparticles were synthesized by solution-phase thermolysis of the diethylammonium salt of the anionic europium dithiocarbamate complex, [Eu(S 2 CNEt 2 ) 4 ] -. Oleylamine and triphenylphosphine were used as surfactants to prevent nanoparticle agglomeration and stabilize particle growth. By varying the synthetic parameters such as reaction temperature, heating time, and the [surfactant]:[precursor] ratio, nanoparticles of different sizes were obtained. The size-dependent magnetic properties of these nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 66 publications
3
63
1
Order By: Relevance
“…What is clear from our data and the literature is that the large increase in magnetization occurs at decreasing temperatures, as a function of particle size [37]. Unfortunately, the evidence for size dependent band gap changes is quite weak.…”
Section: Arrott Plots For Determining the Curie Temperaturesupporting
confidence: 45%
See 3 more Smart Citations
“…What is clear from our data and the literature is that the large increase in magnetization occurs at decreasing temperatures, as a function of particle size [37]. Unfortunately, the evidence for size dependent band gap changes is quite weak.…”
Section: Arrott Plots For Determining the Curie Temperaturesupporting
confidence: 45%
“…For example, an increase of oleylamine and triphenyl phosphine rather than tri-octylphosphine allowed for a reduction in temperature while still producing crystalline nanoparticles. Oleylamine has previously been shown to reduce the decomposition temperature of the dithiocarbamate complexes [59]. Although many semiconductor nanoparticle syntheses use TOP, we found that the need to filter the solvent and the ease of oxidation made TOP less convenient to work with.…”
Section: Nanoparticle Size and Shape Controlmentioning
confidence: 85%
See 2 more Smart Citations
“…ous reports that EuS NCs in the range of 10 nm will have depressed T C values due to surface and quantum effects. 14,16 Using the Curie-Weiss law the Weiss temperature was determined to be 15.7 K which is positive indicating ferromagnetic ordering and similar in magnitude to the reported value of 19 K. 17,18 The effective magnetic moment ͑ eff ͒ is 2.0 B , which is much lower than the 7.9 B expected for pure bulk EuS. As will be discussed in greater detail below, XAS showed there to be 30% of ferromagnetically ordered Eu 2+ and 70% of paramagnetically ordered Eu 3+ present.…”
mentioning
confidence: 99%